Research Status and Prospect of Extreme High Temperature and Drought Events at Home and Abroad - Ma, Lijun (International Journal of Natural Resources and Environmental Studies, 2025)
In recent years, the increasing frequency and intensity of extreme climate events worldwide have attracted widespread attention. Studies have shown that due to climate change caused by human activities, extreme climate events are becoming more common and severe. In China, studies on extreme temperature events have revealed that since the 21st century, extreme high-temperature events have increased significantly, while extreme low-temperature events have shown a decreasing trend. Therefore, geographers at home and abroad are more inclined to study extreme high-temperature and drought events. Such extreme climate changes not only affect the stability of the climate system but also pose challenges to social and economic development. Therefore, to effectively mitigate the impact of climate change on extreme climate events, countries around the world need to work together, strengthen international cooperation, and formulate and implement effective climate change policies and measures. Only through global cooperation can we better protect the global environment and ensure the sustainable development of humans and other organisms.